2021
DOI: 10.3390/cells10113054
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tumor-Derived Exosomes (TEX) in Shaping Anti-Tumor Immune Competence

Abstract: Emerging studies suggest that extracellular vesicles (EVs) mediating intercellular communication in the tumor microenvironment (TME) play a key role in driving cancer progression. Tumor-derived small EVs or exosomes (TEX) enriched in immunosuppressive proteins or in microRNAs targeting suppressive pathways in recipient cells contribute to reprogramming the TME into a cancer-promoting milieu. The adenosinergic pathway is an acknowledged major contributor to tumor-induced immune suppression. TEX carry the compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Arginase 1, HSP27, HSP72, macrophage migration inhibitory factor, galectin 9 and several non-coding RNAs also contribute to the immunosuppressive effects of tumour cell-derived EVs 115 . Furthermore, both the EV-associated adenosine-generating ectoenzymes (CD39 and CD73) and the adenosine cargo of EVs are considered key mediators of immunosuppression in the tumour microenvironment 116 .…”
Section: Antitumour Responsesmentioning
confidence: 99%
“…Arginase 1, HSP27, HSP72, macrophage migration inhibitory factor, galectin 9 and several non-coding RNAs also contribute to the immunosuppressive effects of tumour cell-derived EVs 115 . Furthermore, both the EV-associated adenosine-generating ectoenzymes (CD39 and CD73) and the adenosine cargo of EVs are considered key mediators of immunosuppression in the tumour microenvironment 116 .…”
Section: Antitumour Responsesmentioning
confidence: 99%
“…Under the coordinated regulation of cytosolic proteins, early endosomes sprout to form multivesicular bodies containing multiple intracavity small vesicles, which fuse with the plasma membrane of the cell and release to the outside of the cell through exocytosis, called exosomes ( 1 ). This is the biogenesis and secretion process of exosomes ( Figure 1 ), these exosomes are a type of extracellular vesicles, which contain lipids, proteins, miRNA, and other contents ( 2 ). Exosomes, 30–150 nm nanostructures secreted from donor cells and internalized by recipient cells, can play an important role in the cellular entry of some viruses, these exosomes are actively secreted into various body fluids, including blood, urine, saliva, cerebrospinal fluid, and human breast milk (HBM) ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Adenosine is an important immunosuppressive factor that promotes the exhaustion of NK and T cells in the TME, while the cooperation of CD73 and CD39 can lead to the metabolism of extracellular ATP to adenosine [ 67 69 ]. Lu et al [ 23 ] found that HCC‑derived exosomal circTMEM181 is internalized by macrophages, resulting in the upregulation of CD39 expression.…”
Section: An Excellent Combination Of Exosomes and Circrnasmentioning
confidence: 99%